2020
DOI: 10.1534/g3.120.401661
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Responses and Nutrient Starvation in MCHM Treated Saccharomyces cerevisiae

Abstract: In 2014, the coal cleaning chemical 4-methylcyclohexane methanol (MCHM) spilled into the water supply for 300,000 West Virginians. Initial toxicology tests showed relatively mild results, but the underlying effects on cellular biology were underexplored. Treated wildtype yeast cells grew poorly, but there was only a small decrease in cell viability. Cell cycle analysis revealed an absence of cells in S phase within thirty minutes of treatment. Cells accumulated in G1 over a six-hour time course, indicating arr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 94 publications
3
17
0
Order By: Relevance
“…Natural genetic variation in Aro1 between a sake strain and a European wine strain links nitrogen consumption with growth (Cubillos et al 2017 ). ARO1 mutants are sensitive to many chemicals (Ayers et al 2020 ). While further down the tryptophan branch, trp1 mutants are sensitive to DNA damage (Brown et al 2006 ), detergents (Schroeder and Ikui 2019 ), isobutanol (Liu et al 2021 ), ethanol (Stanley et al 2010 ), cold (Brachmann et al 1998 ; Leng and Song 2016 ), pH (González et al 2008 ), rapamycin (González et al 2008 ), and MCHM (Ayers et al 2020 ).…”
Section: Genetic Variation In Aromatic Amino Acid Biosynthesis Genera...mentioning
confidence: 99%
See 1 more Smart Citation
“…Natural genetic variation in Aro1 between a sake strain and a European wine strain links nitrogen consumption with growth (Cubillos et al 2017 ). ARO1 mutants are sensitive to many chemicals (Ayers et al 2020 ). While further down the tryptophan branch, trp1 mutants are sensitive to DNA damage (Brown et al 2006 ), detergents (Schroeder and Ikui 2019 ), isobutanol (Liu et al 2021 ), ethanol (Stanley et al 2010 ), cold (Brachmann et al 1998 ; Leng and Song 2016 ), pH (González et al 2008 ), rapamycin (González et al 2008 ), and MCHM (Ayers et al 2020 ).…”
Section: Genetic Variation In Aromatic Amino Acid Biosynthesis Genera...mentioning
confidence: 99%
“…ARO1 mutants are sensitive to many chemicals (Ayers et al 2020 ). While further down the tryptophan branch, trp1 mutants are sensitive to DNA damage (Brown et al 2006 ), detergents (Schroeder and Ikui 2019 ), isobutanol (Liu et al 2021 ), ethanol (Stanley et al 2010 ), cold (Brachmann et al 1998 ; Leng and Song 2016 ), pH (González et al 2008 ), rapamycin (González et al 2008 ), and MCHM (Ayers et al 2020 ). These chemicals appear to generate oxidative stress, to which trp mutants are particularly sensitive.…”
Section: Genetic Variation In Aromatic Amino Acid Biosynthesis Genera...mentioning
confidence: 99%
“…Several studies have shown that starvation can induce the oxidative stress [57]. Starvation-induced oxidative stress is closely related to starvation-induced cell toxicity [58][59][60][61]. Furthermore, Sirt3 de- [62][63][64][65].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that starvation can induce the oxidative stress [ 57 ]. Starvation-induced oxidative stress is closely related to starvation-induced cell toxicity [ 58 - 61 ]. Furthermore, Sirt3 deficiency leads to mitochondrial dysfunction and increase the vulnerability of cells to oxidative stress [ 62 - 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…To cope with ROS, yeast cells quickly adjust and synthesize self-healing substanceslike tryptophan. Other than malnutrition, L-Trp has been suggested to be connected to stress tolerance ( Ayers et al, 2020 ). The expressions of genes involved in amino acid synthesis and transportation, such as Prs1 , Prs3 , Tat1 , and Tat2 , must be interrupted to weaken the metabolism of tryptophan and other amino acids.…”
Section: L-trp Regulation Reform S Cerevisiae Stre...mentioning
confidence: 99%